Exploring Graduate Students’ Motivations and Institutional Challenge in Conducting Interdisciplinary Islamic Research at Higher Education - Nuryaman, Nuryaman; Ma’rufah, Hafidhoh; Alamsyah, Randy Putra (EDUKASIA, 2025)
While offering the advantage of addressing complex problems, interdisciplinary researchers still face a range of significant challenges. This study investigates graduate students' motivations and challenges in conducting interdisciplinary Islamic research. This study employed a quantitative survey method using a Likert-scale questionnaire distributed to 106 purposively master's and doctoral students elected at Graduate School of UIN Jakarta, with data analyzed through descriptive statistics. The study found that the primary motivation for students to conduct interdisciplinary research in Islamic studies is the desire to solve complex societal problems, followed by the pursuit of practical solutions and self development, while the motivation for obtaining funding or advancing academic careers rank lowest. Students face challenges, such as differences in scientific disciplines, limited methodological grasp, and knowledge gaps with lecturers and peers. This research contributes to enhance academic curricula and institutional support for fostering effective interdisciplinary research in Muslim-majority contexts.